Imajan dalam puisi Latiff Mohidin - Osman, Ahmad (Universiti Sains Malaysia, 1976)
This is an attempt to appraise the theory and practice of literary imagery in a work of art with particular reference to Latiff Mohidin’s poems. This may lead to a better understanding of contemporary poetry in general, in which in which imagery is an important poetic device. I have called this dissertation, “The Imagery of Latiff Mohidin’s Poems” as images are the most important elements in his poems. This dissertation is divided into six chapters.